Livestock transactions data collection - Grandin, B.E. (International Livestock Centre for Africa, 1983)
Discusses the need for data on voluntary offtake & acquisition of livestock in pastoral production systems, and considers methods through which desired data can be collected, particularly multiple-visit, and single-visit progeny history technique.